On the methods of the statistical theory of control system of production lines - Azarenkov, N. A.; Pihnastyi, O. M.; Khodusov, V. D. (Національний технічний інститут "Харківський політехнічний інститут", 2015)
The analysis of modern methods of organization and management of production is given.
Keywords: production line; PDE-model of production; PDE-model flow production; flow production; optimal control; work in progress